Interest Group Competition and the Organization of Congress: Theory and Evidence from Financial Services Political Action Committees - Kroszner, Randall S.; Stratmann, Thomas (American Economic Review, 1996)
The authors develop a positive theory of how interest-group competition shapes the organization of Congress and use it to explain campaign contribution patterns in financial services. Since interest groups cannot enforce fee-for-service contracts with legislators, legislators have an incentive to create specialized, standing committees which foster repeated dealing between interests and committee members. The resulting reputational equilibrium supports high contributions and high legislative effort for the interests. Contribution patterns by competing interests in the congressional battle over whether banks can enter new businesses support the theory, which also has implications for term limits and campaign reform. Copyright 1998 by American Economic Association.